The Primary Dealer Credit Facility - Antoine Martin; Susan MacLaughlin (Federal Reserve Bank of New York, 2021)
The Federal Reserve established a new Primary Dealer Credit Facility (PDCF) in March 2020, to allow primary dealers to support smooth market functioning and facilitate the availability of credit to businesses and households, in the face of deteriorating conditions in the market for triparty repo financing due to the coronavirus pandemic. A similar facility had been established in March 2008 to help restore the orderly functioning of the market, following the near-bankruptcy of Bear Stearns, and to prevent the spillover of distress to other financial firms. This paper provides an overview of the 2020 PDCF and compares it to the 2008 version.
Keywords: E58; G21; G24; 330; Primary Dealer Credit Facility; COVID-19 pandemic; Federal Reserve lending facilities